2014
DOI: 10.2337/db14-0807
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Glucose-Stimulated GLP-1 Secretion From Perfused Rat Small Intestine

Abstract: Glucose is an important stimulus for glucagon-like peptide 1 (GLP-1) secretion, but the mechanisms of secretion have not been investigated in integrated physiological models. We studied glucose-stimulated GLP-1 secretion from isolated perfused rat small intestine. Luminal glucose (5% and 20% w/v) stimulated the secretion dose dependently, but vascular glucose was without significant effect at 5, 10, 15, and 25 mmol/L. GLP-1 stimulation by luminal glucose (20%) secretion was blocked by the voltage-gated Ca chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
170
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(192 citation statements)
references
References 40 publications
18
170
2
2
Order By: Relevance
“…For example, carbohydrates can be sensed by the T1R2/T1R3 sweet taste receptor found in the gut (Jang et al 2007), although the physiological relevance of sweet taste receptor activation on gut peptide signalling in humans remains debated (Parker et al 2009). Conversely, recent work suggests that GLP-1 release occurs via uptake of glucose coupled with Na + through the sodium/glucose cotransporter member 1 (SGLT1), inducing small currents triggered by increased Na + which leads to membrane depolarization and voltagegated Ca2+ entry, ultimately resulting in GLP-1 secretion (Gribble et al 2003, Kuhre et al 2015. Less is known about intestinal protein sensing, with GPR93, CaSR and PepT1 all being suggested to mediate protein-induced gut peptide release (Nemoz-Gaillard et al 1998, Darcel et al 2005, Liou et al 2011a.…”
Section: Gut Peptide Signalling In Regulating Glucose Metabolismmentioning
confidence: 99%
“…For example, carbohydrates can be sensed by the T1R2/T1R3 sweet taste receptor found in the gut (Jang et al 2007), although the physiological relevance of sweet taste receptor activation on gut peptide signalling in humans remains debated (Parker et al 2009). Conversely, recent work suggests that GLP-1 release occurs via uptake of glucose coupled with Na + through the sodium/glucose cotransporter member 1 (SGLT1), inducing small currents triggered by increased Na + which leads to membrane depolarization and voltagegated Ca2+ entry, ultimately resulting in GLP-1 secretion (Gribble et al 2003, Kuhre et al 2015. Less is known about intestinal protein sensing, with GPR93, CaSR and PepT1 all being suggested to mediate protein-induced gut peptide release (Nemoz-Gaillard et al 1998, Darcel et al 2005, Liou et al 2011a.…”
Section: Gut Peptide Signalling In Regulating Glucose Metabolismmentioning
confidence: 99%
“…A few reports have shown that glucose stimulates NT secretion in healthy young humans (18) and from isolated perfused rat small intestine (4), but the underlying mechanisms of secretion are not well understood. Studies of secretion of the gut hormone glucagonlike peptide-1 (GLP-1) have indicated that glucose-stimulated secretion of this hormone involves electrogenic sodium uptake through sodium-glucose transporter 1 (SGLT1) as well as closure of ATP-sensitive potassium (K ATP ) channels (6,17,21,24). Recent findings indicate that some enteroendocrine cells have substantial similarities in respect to expression of glucose transporters and molecular glucose sensors (5, 8).…”
mentioning
confidence: 99%
“…In addition, luminal glucose administration acutely stimulates GLP-1 secretion from isolated perfused mouse intestines [3]. Similar results were obtained when glucose was perfused into segments of the small intestines of rats, dogs, and pigs, in which luminal glucose infusion stimulates GLP-1 secretion [4]. The stimulating secretion mechanism of luminal glucose has been extensively investigated.…”
mentioning
confidence: 53%
“…The result coincides with Hansen' study [12], which reported that the perfusate glucose concentration (3.5, 5, and 11 mmol/L) influences the amount of GLP-1 secreted, using isolated preparation of porcine ileum. Kuhre study also showed that Luminal glucose (5% and 20% w/v) stimulated GLP-1 secretion dose dependently [4].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation